Investigating the effect of learning and motivational strategies on the self-efficacy of physical education and sports science students with the mediating role of academic progress and enthusiasm - Ahmad Sabihabdollah Alharishavi; Hasan ghalavandi; Mohammad hassani (مدیریت و چشم انداز آموزش)
AbstractThe purpose of this research is to investigate the effect of learning and motivational strategies on the self-efficacy of physical education and sports science students with the mediating role of academic progress and enthusiasm. This research is applicable in terms of purpose, and descriptive-correlative in terms of nature, with path analysis approach. The statistical population of the research includes 250 students of the field of physical education and sports sciences of Iraq University; 150 of whom were selected by simple random sampling using Cochran's formula. To collect research data, five standard questionnaires was used as follows; learning and motivational strategies by Pintrich and de Groot (1990), academic achievement goals by Middleton and Midgley (1998), academic enthusiasm by Fredericks et al. (2004), and educational self-efficacy of Morris (2001). The face and content validity of the questionnaire was approved by experts and confirmed through factor analysis. The reliability of the tool was confirmed using Cronbach's alpha coefficient in a preliminary study for the learning strategies questionnaire 0.88, motivational strategies 0.91, academic achievement goals 0.87, academic enthusiasm 0.91, and academic self-efficacy 0.86. Data analysis was done using Pearson's correlation coefficient analysis and path analysis in SPSS and Lisrel statistical software. The results showed that the effect of learning and motivational strategies, academic achievement goals and academic enthusiasm on students' academic self-efficacy was positive and significant. It was also found that the mediating role of academic achievement goals and academic enthusiasm in the effect of learning and motivational strategies on academic self-efficacy was positive and meaningful.Extended abstractIntroductionThrough the sports fields of physical education and educational sciences, students are introduced to sports and health activities, and by learning basic movement skills, it is expected that they will pay more attention to their physical and mental health after graduation and make sports a part of their daily program (Al-Yudawi, 2020). The findings show that if the pattern of physical activity is established during the student years, it will remain stable in the years after graduation. It is worth mentioning that the students of these sports fields spend a significant amount of time motionless in the classroom studying and using the computer and the Internet during their daily studies, and it is expected that they will join sedentary occupations in the future as well (Limani et al, 2022). In addition, physical education and sports science students are usually familiar with the principles of physical activity theoretically and are expected to participate in physical activity programs with interest and volunteering after completing the curriculum, which is one of the main goals of their study units (Majnoni, 2022). The general goals of these courses are to familiarize with the concepts of physical education and sports science and its role in individual and social life, to learn the methods of maintaining health and body proportions, to learn the principles of physical movements, to learn and acquire skills related to basic sports movements, and to create appropriate sports opportunities. The results of research in this field show that physical education and sports science professors are facing many problems, including not having many facilities, large number of students, not having sports space, lack of time, lack of motivation, lack of seriousness of students, lack of sports equipment, lack of attention from officials, lack of Planning, not having the necessary specialization, and the interference of classrooms (Dehghan Ghahfarokhi & Godarizi, 2020).Therefore, the present research seeks to evaluate this research problem: whether learning and motivational strategies with the mediating role of achievement goals and academic enthusiasm have any effect on the self-efficacy of physical education and sports science students?Theoretical FrameworkEfficacySelf-efficacy as one of the motivational variables, due to internal motivation, causes a person to work spontaneously in the environment and achieve his own efficiency beliefs (Afangideh, 2022).Learning strategiesOne of the effective factors in facilitating and improving learning is paying attention to learning strategies. Any method or strategy that helps to process information and facilitate learning is called learning strategies (Rajab pour Mohahrani, 2022).Progress goalsIt is a cognitive-social frame of mind that guides a person in interpreting situations, processing information, facing tasks, and dealing with challenges (Kaplan & Flum, 2010). Achievement goals refer to a person's objective orientations and are the student's cognitive representation of the reasons for engaging in achievement-related behaviors and the norms he uses to judge or evaluate performance. Goal orientation or goal progress is one of the most up-to-date topics that have attracted the attention of theorists and researchers in the field of motivation for progress.Passion for educationAcademic enthusiasm refers to behaviors that are related to learning and academic progress, and refers to the quality of effort that learners spend on targeted educational activities to directly contribute to achieving desired results (Wittrup et al, 2019).Hosseini (2023) investigated the role of motivational strategies in predicting academic progress and self-efficacy in middle school male students. It was found that the role of motivational strategies in predicting academic progress and self-efficacy in students is positive and significant.Wei et al, (2023) investigated the identification of the role of motivation, perceived learning support, learning participation, and self-regulated learning strategies. They reported that self-regulated learning strategies have a positive and significant effect on learners' perceived learning outcomes from online courses. Research methodologyThis research is applicable in terms of purpose, and descriptive-correlative in terms of nature, with path analysis approach. The statistical population of the research includes 250 students of the field of physical education and sports sciences of Iraq University; 150 of whom were selected by simple random sampling using Cochran's formula. To collect research data, five standard questionnaires was used as follows; learning and motivational strategies by Pintrich and de Groot (1990), academic achievement goals by Middleton and Midgley (1998), academic enthusiasm by Fredericks et al. (2004), and educational self-efficacy of Morris (2001). The face and content validity of the questionnaire was approved by experts and confirmed through factor analysis. The reliability of the tool was confirmed using Cronbach's alpha coefficient in a preliminary study for the learning strategies questionnaire 0.88, motivational strategies 0.91, academic achievement goals 0.87, academic enthusiasm 0.91, and academic self-efficacy 0.86.Research findingsData analysis was done using Pearson's correlation coefficient analysis and path analysis in SPSS and Lisrel statistical software. The results showed that the effect of learning and motivational strategies, academic achievement goals and academic enthusiasm on students' academic self-efficacy was positive and significant. It was also found that the mediating role of academic achievement goals and academic enthusiasm in the effect of learning and motivational strategies on academic self-efficacy was positive and meaningful. ConclusionThe present study was conducted with the aim of the effect of learning and motivational strategies on the self-efficacy of physical education and sports science students with the mediating role of academic progress and enthusiasm.. The results of these findings are consistent with the results of Samiee Zafarghandi et al., 2021), Wei et al, (2023), Tseng et al, (2022), Hayat et al., (2020), El-Adl & Alkharusi (2020), Hossin (2023), Fouladi far et al., (2021), Alhadabi & Karpinski (2020), Suter et al., (2022), Sayadi & Solimani (2022), Lobos et al., (2021), Shing & Rameli, (2020), Janke (2022), Sheu et al., (2022), and Siddiq et al., (2020). Alhadabi & Karpinski (2020) showed that the relationship between progress orientation goals and learners' self-efficacy is positive and significant.